La nutrición infantil en el desarrollo de los procesos cognitivos en los niños de cuarto grado de la Unidad Educativa Camilos Gallegos Toledo de la ciudad de Riobamba- periodo lectivo 2022 al 2023 - Horna Berrezueta, Gregory Levy (2024)
The thesis entitled "Child Nutrition in the Development of Cognitive Processes in fourth-grade Children of the 'Camilo Gallegos Toledo' Educational Unit in the City of Riobamba - school year: 2022 to 2023" addresses the impact, its importance, and the factors of nutrition in the cognitive development of fourth-grade children. A qualitative methodology and non-experimental design were used, with surveys addressed to 35 parents. The results show that parents know little about the importance of a balanced diet for their children. The need for collaboration between parents and teachers emphasizes the improvement of the conditions that affect cognitive development. Therefore, the implementation of a nutritional guide is suggested to improve nutrition and promote health in the academic performance and educational growth of children.